Comparative Evaluation of Three-Tier and Cisco ACI Data Center Architectures - Andi Muhammad Bintang Fadhilah; Ari Ramadhan (Journal La Multiapp, 2026)
This study aims to conduct a comprehensive comparative evaluation of traditional three-tier and application-centric data center network architectures within an enterprise environment. The research adopts a descriptive qualitative approach using a comparative case study design combined with design evaluation techniques. Empirical data were collected from a real-world data center operating both architectures concurrently across multiple sites, supported by documentation analysis, operational monitoring, and direct observation. The analysis is structured around five key capability dimensions, namely scalability, security, reliability, operational simplicity and agility, as well as network visibility and virtualization awareness. The findings demonstrate that the application-centric architecture significantly outperforms the traditional model in scalability, security, operational efficiency, and visibility. It supports a higher number of endpoints and nodes with lower resource utilization, achieves reduced network latency, enables fine-grained security segmentation, and provides centralized policy-based management with integrated monitoring capabilities. Although the traditional architecture shows slightly higher aggregate availability, this is primarily influenced by operational maturity rather than architectural superiority. The results indicate that the application-centric approach offers a more adaptive, scalable, and secure solution for modern enterprise data center environments. This study contributes practical insights for network engineers and decision-makers by providing an evidence-based evaluation framework and highlighting key considerations for infrastructure transformation strategies.